POVERTY PROBLEM: SOCIAL CONTEX - Oliynyk, Halyna (Social work and education, 2017)
Poverty as a global social phenomenon exists in all countries all over the world and Ukraine is not an exception. The problem of poverty is an extremely topical problem and the theme of the present because every fourth person in our country lives in conditions of poverty. Poverty is impossibility due to the lack of funds to support a lifestyle which is characteristic of a particular society, in a particular period. This means that the poor cannot eat properly, pay for housing and utilities, treat and rest, learn themselves and provide tuition fees for their children. The main reason for poverty is low income. Poverty is defined as the impossibility of maintaining a lifestyle in a particular society at a specific time due to the lack of funds. The poor sections of society include those who are not deprived of their own free will: normal housing, food, clothing, health, education.The problem of poverty is so urgent that many other problems are being reduced to it. Demographics, employment, unemployment is directly related to poverty. Poverty has a direct impact on the health of the population, the level of education and culture of citizens, their upbringing, socialization and morality, it is one of the factors preventing the development of science. Poverty contributes to the dehumanization of human relations, the growth of crime and terrorism, and leads to a decrease in the level and quality of life. It specifically affects political relations; the implementation of state policy at all levels, and impedes the formation of civil society.